Geological observations along motor road from Butwal to Ramdighat, central Nepal - Arita, Kazunori; Yoshida, Mitsuo (Journal of Nepal Geological Society, 1982)
The present paper briefly deals with the lithostratigraphy and structure of the area along the motor road between Butwal and Ramdighat in central Nepal. The area consists geologocally of six formations from the base upwards the Angaha Khola Formation, Ramdi Formation. Kokat formation, Kerabari formation, Charchare Formation and Tansen Formation. The lower four formations are considered to be lower to middle paleozoic and the upper two formations to be upper Mesozoic in age. These formations are distinct from the Midland meta- sediment Group to the north. The Tansen zone composed of these formations, as well as the Piuthan zone on the west, is a peculiar geologic unit of the Nepal Himalayas.